Determination of creatine and phosphocreatine in muscle biopsy samples by capillary electrophoresis with contactless conductivity detection - See, Hong Heng (2012)
A capillary electrophoresis method with contactless conductivity detection was evaluated as a new approach for quantification of creatine and phosphocreatine in human quadriceps femoris biopsy samples. The running buffers employed consisted of 1 M acetic acid at a pH of 2.3 for the determination of creatine and 50 mM 3-(N-morpholino)propanesulfonic acid/30 mM histidine at a pH of 6.4 for the determination of phosphocreatine in the centrifuged muscle extracts. The limits of detection for creatine and phosphocreatine were found to be 2.5 and 1.0 μM, respectively. Creatine and phosphocreatine were determined in six human muscle biopsy samples and the results were found comparable to those of a standard enzymatic assay. The procedures developed for creatine and phosphocreatine also allow the determination of creatinine as well as adenosine diphosphate and adenosine triphosphate.